Spontaneous Object Exploration in a Recessive Gene Knockout Model of Parkinson’s Disease: Development and Progression of Object Recognition Memory Deficits in Male Pink1–/– Rats - Pinizzotto, Claudia C.; Dreyer, Katherine M.; Aje, Oluwagbohunmi A.; Caffrey, Ryan M.; Madhira, Keertana; Kritzer, Mary F. (Frontiers in Behavioral Neuroscience, 2022)
Cognitive impairments appear at or before motor signs in about one third of patients with Parkinson’s disease (PD) and have a cumulative prevalence of roughly 80% overall. These deficits exact an unrelenting toll on patients' quality and activities of daily life due in part to a lack of available treatments to ameliorate them. This study used three well-validated novel object recognition-based paradigms to explore the suitability of rats with knockout of the PTEN-induced putative kinase1 gene (Pink1) for investigating factors that induce cognitive decline in PD and for testing new ways to mitigate them. Longitudinal testing of rats from three to nine months of age revealed significant impairments in male Pink1-/- rats compared to wild type controls in Novel Object Recognition, Novel Object Location and Object-in-Place tasks. Task-specific differences in the progression of object discrimination/memory deficits across age were also seen. Finally, testing using an elevated plus maze, a tapered balance beam and a grip strength gauge showed that in all cases recognition memory deficits preceded potentially confounding impacts of gene knockout on affect or motor function. Taken together, these findings suggest that knockout of the Pink1 gene negatively impacts the brain circuits and/or neurochemical systems that support performance in object recognition tasks. Further investigations using Pink1-/-rats and object recognition memory tasks should provide new insights into the neural underpinnings of the visual recognition memory and visuospatial information processing deficits that are often seen in PD patients and accelerate the pace of discovery of better ways to treat them.